A Family Education Model Based on Affection to Improve Children's Psychological Well-Being - Su'udin Aziz (Badan Usaha Milik Desa Berkaho Pungpungan, 2025)
This research is motivated by the weakening quality of emotional interactions within modern families, which has led to an increase in psychological problems among children, such as anxiety, low self-esteem, and an inability to manage emotions. This condition highlights the importance of a family education model that does not merely emphasize cognitive aspects or discipline, but also prioritizes affection as a fundamental basis for children’s psychological well-being. This study employs a library research method by collecting, reviewing, and synthesizing various scientific literatures related to family education, child developmental psychology, theories of affection, and psychological well-being. Data analysis was conducted through content analysis to identify patterns, key concepts, and relationships among relevant variables. The results indicate that affection-based family education plays a significant role in shaping emotional stability, psychological resilience, and children’s moral and social development. Six main components were identified in this model, namely empathetic communication, psychological support, moral-emotional role modeling, consistent parental presence, non-violent parenting, and a safe and harmonious family environment. This model is proven to be relevant in addressing the challenges of modern families facing digital pressures, social changes, and increasing emotional needs of children. The implications of this research emphasize that parents need to enhance their literacy in affection-based parenting as a primary strategy for building children’s psychological well-being. In addition, the findings can serve as a reference for educators, counselors, and policymakers in designing more humane family education programs oriented toward children’s mental health. Thus, this study makes an important contribution to the development of a comprehensive and relevant family education model in the modern era.